A Morphological Study On Compound Words In English Translation Of Al- Qur'an - Oktiana, Kristin; , Dra. Dwi Haryanti, M. Hum; , Siti Fatimah, S. Pd, M. Hum (2013)
This research paper is aimed at answering two problems, namely the variation forms of compound word found in English Translation of Al- Qur' an, and the meanings of the compound found in English Translation of Al- Qur' an. The data are taken from English Translation of Al- Qur' an. To find the answer of the forms, the writer uses the theory of O'Grady and finds the meaning of compound uses the theory of Palmer. The type of this research paper is descriptive qualitative research. In collecting the data, the writer applied documentation method. The several steps are done to analyze the data such as reading and collecting the data. In analyzing the form of compound word, the step is analyzing by employing the tree diagram. Based on the analyzed data taken from the English Translation of Al- Qur'an there are two findings. The first finding shows that there are 72 (100%) data of compound words, consist of noun compound (14 or 19.4 %), verb compound (38 or 52.8 %), adjective compound (8 or 11.1 %) and preposition compound (12 or 16.7 %). The second finding shows the meaning of compound word consists of transparent meaning (43 or 63.8 %) and opaque meaning (26 or 36.2 %). Total is 72 (100 %).